2013
DOI: 10.1016/j.jvs.2013.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Association of race and socioeconomic status with the use of endovascular repair to treat thoracic aortic diseases

Abstract: Objective Descending thoracic aortic diseases may be treated with either open thoracic aortic repair or thoracic endovascular aortic repair (TEVAR). Previous studies have demonstrated that race and socioeconomic status (SES) affect access to care and treatment allocation in vascular surgery. We hypothesized that racial minorities and lower SES patients have decreased propensity to have their thoracic aortic disease treated with TEVAR. Methods Weighted discharge records for patients who underwent either open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…For TEVAR specifically, Johnston et al 8 concluded that traditional racial disparities do not persist in TEVAR allocation between multiple races (e.g., White, Black, Hispanic, Asian or Pacific Islander, Native American), which is in line with the present study that observed that Black people have increased access to TEVAR over the last years. Moreover, a recent report by Yin et al 9 found lower 30-day and 1-year mortality rates in Black patients as compared to White patients treated with TEVAR for aortic aneurysm or aortic dissection.…”
supporting
confidence: 91%
“…For TEVAR specifically, Johnston et al 8 concluded that traditional racial disparities do not persist in TEVAR allocation between multiple races (e.g., White, Black, Hispanic, Asian or Pacific Islander, Native American), which is in line with the present study that observed that Black people have increased access to TEVAR over the last years. Moreover, a recent report by Yin et al 9 found lower 30-day and 1-year mortality rates in Black patients as compared to White patients treated with TEVAR for aortic aneurysm or aortic dissection.…”
supporting
confidence: 91%
“…and patients with lower median household incomes had a higher propensity for undergoing TEVAR procedures. 9 We could observe a relative increase in the TEVAR incidence rate during 2013-2015 for the Black population in this opportunity. This trend could be related to some national health reforms implemented during the same period.…”
Section: Discussionmentioning
confidence: 73%
“…11 This paradigm was challenged by two reports, including data from 1999 to 2008, where we could observe a setting-off of traditional racial disparities with TEVAR utilization. 8,9 Given that more than a decade has already passed, our objective is to reevaluate if TEVAR continues to be a procedure where access to surgical services is not affected by racial differences using a contemporary database.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The rapidly expanding use of thoracic endovascular aortic repair over open repair provides a recent example of a revolutionary cardiovascular technology. Johnston and colleagues 25 reported that counter to their hypothesis, racial/ethnic minorities and patients with lower socioeconomic status were more likely to receive thoracic endovascular aortic repair over traditional open repair despite a previously described baseline disparity. Even after controlling for baseline comorbidity and treatment indication, they reasoned that greater disease severity and aneurysm morphology might not have been fully captured in their statistical controls, leading vulnerable populations to preferentially undergo the less invasive therapy.…”
Section: Discussionmentioning
confidence: 93%